Effects of Sexual Behavior, Family Support, Peer Support, Stigma, and Discrimination on Quality of Life Among Gay Community in Tulungagung, East Java - Dily Ekasari; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, 2018)
Background: Stigma and discrimination that are experienced by gay community have long been documented to occur in Indonesia, including Tulungagung District, East Java. Gay community often experience stigma, discrimination, and rejection by the society and health personnel. Stigma and discrimination may worsen the quality of life among gay community. This study aimed to examine the effects of sexual behavior, family support, family income, peer support, stigma, and discrimination on quality of life among gay community in Tulungagung, East Java.Subjects and Method: This was an analytic observational study with cross-sectional design. The study was conducted in Pelangi Gay Community, Tulungagung District, from October to November, 2017. A total sample of 181 gays was selected by stratified random sampling. The exogenous variables were sexual behavior, family income, peer support, stigma, and discrimination. The endogenous variables were family support and quality of life. The data were collected by questionnaire and analyzed by path analysis.Results: Better quality of life was positively affected by safe sexual behavior (b= 1.32; 95% CI= 0.18 to 2.46; p= 0.023) and strong family support (b= 1.47; 95% CI= 0.42 to 2.51; p= 0.006). Strong family support was positively affected by family income (b= 1.62; 95% CI= 0.97 to 2.27; p= 0.001). Better quality of life was positively affected by participation in peer support program (b= 2.84; 95% CI= 1.77 to 3.91; p= 0.001), freedom of stigma (b= 1.11; 95% CI= -0.04 to 2.26; p= 0.060), and freedom of discrimination (b= 1.43; 95% CI= 0.37 to 2.48; p= 0.008).Conclusion: Safe sexual behavior and strong family support have direct positive effect on the quality of life among gay community. Stigma and discrimination have indirect effect on lower quality of life among gay community.Keyword: quality of life, sexual behavior, family support, stigma, discrimination, gayCorrespondence: Dily Ekasari. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: dilyekasari89@gmail.com.Journal of Epidemiology and Public Health (2018), 3(1): 50-59https://doi.org/10.26911/jepublichealth.2018.03.01.04